Evaluasi Dampak Change Order terhadap Biaya dan Waktu menggunakan Metode EVM - Ahmad Nurjaman; Ganjar Jojon Johari (Jurnal Konstruksi, 2026)
Design changes (change orders) are a common challenge in construction projects because they can affect cost, schedule, and quality. This study aims to identify the types of design changes, their causal factors, and their impacts on cost and schedule performance using the Earned Value Management (EVM) approach. A case study was conducted on the renovation project of the BTN Bank KCP Sepaku Building, which experienced 14 Site Instructions (SI) and 1 Contract Change Order (CCO). The results show that design changes occurred in architectural, structural, and MEP works, leading to additional work volumes, rework, and adjustments to work sequencing. The main contributing factors include discrepancies between existing site conditions and design drawings, additional requirements from the owner, delays in design approvals, and adjustments to technical regulations. EVM analysis indicates that the project experienced deviations in the second week, with an SPI of 0.78 and a CPI of 0.95, indicating schedule delays and cost inefficiency. However, from weeks four to seven, performance gradually improved, and the final EAC was recorded at IDR 3,662,040,000, equal to the BAC, meaning the project was completed on time without cost overruns. The study recommends thorough design verification at the early stages, cross-party coordination, and EVM-based control to minimize deviation risks in similar projects. The practical implication of this research is to provide guidance for contractors and project managers in implementing cost and schedule control strategies when facing design changes.